Grave Breaches and Justifications: The War Crime of Forcible Transfer or Deportation of Civilians and the Exception for Evacuations for Imperative Military Reasons - Emma Brandon (Oslo Law Review)
The Fourth Geneva Convention prohibits the forcible transfer or deportation of civilian populations and classifies this action as a grave breach of the laws of war. However, attempts to prosecute this grave violation are hindered by an exception for evacuations of the civilian population for imperative military reasons, which has yet to be satisfactorily defined, either in scholarly literature or in the law. This article analyses the drafting history of the Geneva Convention provisions, the practice of international tribunals, the practice of States, and the practice of international and regional human rights organisations to establish a concrete definition of this exception so that international criminal prosecutors can prosecute confidently this grave war crime and defendants are assured of appropriate notice of all elements of this crime.